Web-Based Project Work Management Information System Development (Case: CV. Trijaya Abadi Electric) - Arsyad Maulana , Faruq; Wibawa, Wibawa; Kusuma Wardana , Ari (APPLIED SCIENCE AND TECHNOLOGY REASERCH JOURNAL, 2023)
This research was conducted to build a System Information Management Project with efficient, effective, and easy as well as can count budget work, budget shopping, budget wages employees, Manage presence employees, count payroll in a way, got it make report payroll. and reports readiness Work on discussion budget. This research was carried out through four stages, namely 1. Planning ( planning ), 2. Analysis ( analysis ), 3. Design ( designing ), and 4. Implementation ( application ). Development System Information Management Work Project Web Based ( Case Study: CV. Trijaya Abadi Electric). CV. Trijaya Abadi Electric has so far managed everything related to work, still using manual systems such as employee absences verbally to superiors, work progress verbally, payroll still using Microsoft Excel, and work management that has not been fully organized causing data input errors. and budget calculations that are often missed, resulting in errors in invoices and tender notes. The process of calculating the shopping budget and equipment rental along with worker salaries must be maximum and optimal so that there are no errors in the bookkeeping so that it is clear that the profits obtained are in accordance with the calculations.